2018
DOI: 10.29271/jcpsp.2018.02.122
|View full text |Cite
|
Sign up to set email alerts
|

Role Of Weight-bearing Exercises In The Treatment Of Post-menopausal Osteoporosis

Abstract: The physical activity along with medication play vital role in the treatment of post-menopausal osteoporosis than medication alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Based on the modified Jadad scale tool, 19 articles had acceptable or good quality[ 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 ] while the quality of 9 articles was poor[ 41 42 43 44 45 46 47 48 49 ] [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the modified Jadad scale tool, 19 articles had acceptable or good quality[ 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 ] while the quality of 9 articles was poor[ 41 42 43 44 45 46 47 48 49 ] [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exercise with medication was showed more improvement. 18 Low level laser therapy with pulsed electromagnetic therapy improve bone mineral density in elderly with primary osteoporosis (P<0.001). [22] This current study showed that 4% physiotherapist used the laser therapy for the treatment of osteoporosis patients as well as 40% therapist used electrotherapy to treat this condition.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines osteoporosis as a gradual systemic skeletal illness in which mineral density of bones is lowered, structure of bone changed at cellular level causing weakness of bones which increases the risk of fractures and physical disability and the need for long term care. [1,2] Osteoporosis that causes fracture characterize a severe and immoderate public health issues leading to functional impairment and increased death risk. [3] In women, the prevalence of osteoporosis was reported to be 9% in the United Kingdom, 15% in France and Germany, 38% in Japan and 16% in the United States, whereas in men, the prevalence was 1% in the United Kingdom, 3% in Canada, 4% in Japan and 8% in France.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an opportunity for the HIV and rehabilitation sector to learn and apply evidence from other illnesses such as chronic obstructive pulmonary disease43 and fibromyalgia,44 and in older adults living with multimorbidity,45 as well as applying principles from models of HIV rehabilitation established in other contexts such as low-income to middle-income countries 30 42. As more people age with HIV in combination with other chronic conditions, it will be important to draw from evidence on the effect of PT interventions from other chronic conditions such as chronic obstructive pulmonary disease,46 diabetes47 and osteoporosis,48 and apply it to the context of people with HIV in the outpatient care setting.…”
Section: Discussionmentioning
confidence: 99%